Doctor Illuminatus : A Ramon Llull Reader. - Llull, Ramón (Princeton University Press, 1993)
For this new anthology, Anthony Bonner has chosen central texts from his acclaimed two-volume compilation Selected Works of Ramon Llull (Princeton, 1985). Available for the first time in an affordable format, these works serve as an introduction to the life and writings of the Catalan (properly, Majorcan) philosopher, mystic, and theologian who lived from 1232 to 1316. Founder of a school of Arabic and other languages, Llull was also a poet and novelist and one of the creators of literary Catalan. This volume contains three prefaces on Llull's life, thought, and reputation. Of Llull's works, it offers Book of the Gentile and the Three Wise Men, his seminal Christian apology; the Ars brevis, a summary of his philosophical system; The Book of the Lover and the Beloved, a celebration of mystical love in the courtly tradition; and his wittily scathing Book of the Beasts.
Description based upon print version of record.
Keywords: Philosophy -- Early works to 1800.; Theology -- Early works to 1800.; Apologetics -- Early works to 1800.; Mysticism -- Early works to 1800.; Philosophie -- Ouvrages avant 1800.; Théologie -- Ouvrages avant 1800.; Apologétique -- Ouvrages avant 1800.; Mysticisme -- Ouvrages avant 1800.; Theology; Philosophy; Mysticism; Apologetics; Early works